Tradisi Lisan Pada Pernikahan Adat Masyarakat Melayu Deli di Deli Serdang Sumatera Utara - Hummaira, Nabila Devia; Chahyani, Ayu Tri (Literasi Bahasa dan Sastra Jurnal, 2025)
This study examines the role of pantun as an oral tradition in Deli Malay wedding ceremonies, focusing on the values ​​contained within it and efforts to revitalize the tradition. This analysis examines the formula in Deli Malay wedding pantun based on Albert Lord's theory of oral tradition. The research method used is a qualitative approach, involving interviews, observation, and documentation to explore the meaning and function of pantun in a social and cultural context. The results show that wedding pantun contains the values ​​of faith, honesty, responsibility, and cooperation, which function as a means of conveying moral and ethical messages. In addition, this oral tradition plays an important role in strengthening social ties between families and communities. However, the study also found a degradation of the meaning of pantun due to modernization and a lack of understanding of cultural values ​​among the younger generation. Therefore, revitalization efforts through education, training, and the use of digital media are essential to maintain the sustainability of the pantun tradition. This research is expected to contribute to the preservation of Deli Malay culture and increase public awareness of the importance of oral traditions.